Posture and Balance: Study Case - Quka, Najada (European Journal of Multidisciplinary Studies, 2022)
Most of the postural problems are detected mostly as symptoms of muscular imbalance influenced by a variety of risk factors which can be internal or external factors. Through this study, we investigate how important a good posture is for a better balance stability by evaluating the impact of posture corrective exercises over the equilibrium parameter. Our study was conducted over randomly selected 67 children aged 10-11 years. Over randomly selected 34 children we used an Intervention Program (the isometric and stretching exercises) while the rest followed the routine of physical education class program. For the review we used Jab Ref, Pub Med, Medline, and Research Gate. To evaluate the postural shape of children we used “Posture Screen Mobile®-PSM (iPod) and Postural Analysis Grid Chart” and the Leonardo Mechanograph® GRFP for the equilibrium parameters. To analyze the data, we applied the SPSS 20.0 applying the Paired-Sample Test (T-test) and the Multifunctional Linear Regression. The results showed an efficacy of the postural corrective exercises on the posture alignment improvement and the equilibrium parameters too. In the end, we underline the importance of these kind of exercises to be implemented on the physical education program in order to insure a better posture and equilibrium too.